1994
DOI: 10.1073/pnas.91.13.6002
|View full text |Cite
|
Sign up to set email alerts
|

Loss of receptors for transforming growth factor beta in human T-cell malignancies.

Abstract: Ki-1 (CD30)+ cute T-cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
114
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(119 citation statements)
references
References 37 publications
4
114
0
Order By: Relevance
“…Several studies have shown that inactivation of TGF␤ receptors induces TGF␤ resistance and contributes to disease pathogenesis (21,22). In OA, dysfunction of TGF␤1 signaling may contribute to an insensitivity to TGF␤1 and lead to the degradation of articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that inactivation of TGF␤ receptors induces TGF␤ resistance and contributes to disease pathogenesis (21,22). In OA, dysfunction of TGF␤1 signaling may contribute to an insensitivity to TGF␤1 and lead to the degradation of articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Second, decreased expression of either TbRI or TbRII has been implicated as a mechanism for TGF-b resistance in human tumors. TbRI underexpression occurs in prostate, colon, and pancreatic cancer cell lines, and in chronic lymphocytic leukemia cells (Baldwin et al, 1996;DeCoteau et al, 1997;Kim et al, 1996;Wang et al, 1996), whereas TbRII levels are low in gastric cancer cells and in TGF-bresistant T-cell lymphoma cells (Kadin et al, 1994;Park et al, 1994). Third, inactivating mutations in components of the TGF-b signaling pathway, such as Smad2 or Smad4 lead to a TGF-b-resistant state Eppert et al, 1996;Riggins et al, 1996;.…”
Section: Discussionmentioning
confidence: 99%
“…However, a strong correlation between TGF-b RII mutation and microsatellite instability has been demonstrated, only for colon and gastric cancers (Eshleman and Markowitz, 1995;Kolodner, 1996;Markowitz et al, 1995;Modrich and Lahue, 1996;Myero et al, 1995;Parsons et al, 1995). Since then, defective expression of TGF-b RII has been demonstrated in gastric, colon, small-cell lung, breast, endometrial, hepatocellular, bladder, and squamous cell cancers as well as retinoblastoma, pheochromocytoma, osteosarcoma, and lymphomas (Chang et al, 1997;Garrigue-Antar et al, 1995;Inagaki et al, 1993;Kadin et al, 1994;Kim and Kim, 1996;Kimchi et al, 1988;Park et al, 1994;Markowitz et al, 1995;Markowitz and Roberts, 1996;Sun et al, 1994;Wang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%